PPDB System Innovation: Building Quality Education Through Equitable Access - Laely Purnamasari; Heri Ginanjar (Jurnal Intelek Insan Cendikia, 2025)
This research examines the implementation of innovations in the New Student Admission System (PPDB) in the context of equalizing educational access in Indonesia. Using a qualitative approach with descriptive-analytical methods, this research involves in-depth interviews with stakeholders, field observations, and documentation studies. The results show that digital transformation in the PPDB system has improved transparency and administrative efficiency, although digital divide challenges remain in some regions. The implementation of the zoning system shows varied results, with higher success rates in urban areas compared to rural areas. Local innovations such as community-based assistance and mobile help desks have become adaptive solutions in addressing region-specific constraints. This research recommends the importance of strengthening digital infrastructure, improving human resource capacity, and developing policies that are adaptive to local needs to achieve better equalization of educational.